Satisfaction and attitudes of the student population about dental aesthetics (Journal of Health Sciences, 2021)
Introduction: Perceptions of the esthetic appearance of teeth vary in different individuals and can affect satisfaction with the dental appearance, attitudes, and the need for appropriate dental treatment. The research aims to examine the factors influencing the satisfaction with the appearance of the dentition and the attitude toward treatments which improve dental esthetics among students of the faculty of dentistry in comparison to the attitudes of students of non-dental faculties.Methods: The research included a total of 358 students of the Faculty of Dentistry and Faculty of Architecture in Sarajevo who voluntarily filled out a questionnaire created for this research. The questionnaire contained questions related to satisfaction with the appearance of teeth in general, tooth color, tooth position, questions related to the previous, and future desired esthetic restorations and treatments.Results: Female subjects expressed statistically significantly greater dissatisfaction with the appearance of the dentition and did or plan to do treatments that could improve dental esthetics compared to male subjects. Students of the Faculty of Dentistry at final years were significantly more satisfied with the general appearance of teeth and tooth color compared to freshmen students of the Faculty of Dentistry and students of the Faculty of Architecture.Conclusion: Satisfaction with dental appearance is a subjective experience that is influenced by various factors, level, and type of education is among them.